PENGARUH AUDIT INTERNAL, PENGAWASAN DAN PENGENDALIAN TERHADAP PENCEGAHAN KECURANGAN KAS PADA PUSKESMAS MEURAXA KOTA BANDA ACEH - Nurhayati Nurhayati; Eliana Eliana; Ainul Ridha; Yusni Hervy Yusuf; Syarifah Mauli Masyitah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2022)
The purpose of the study was to determine whether internal audit, supervision and control simultaneously affect the prevention of cash fraud at the Meuraxa Health Center in Banda Aceh City. This study uses a total sample (census), where all members of the population are used as samples. This is often done because the population is small, less than 100 people, so the sample of this study is 52 people. The results show that internal audit, supervision and control simultaneously and partially affect the prevention of cash fraud at Meuraxa Health Center Banda Aceh City. Konstanta (α) of 9.031 which means that if the variables of Internal Audit, Supervision and Control are considered constant, then the amount of cash fraud prevention at the Meuraxa Health Center in Banda Aceh City is 9.031%. the correlation coefficient (R) is 0.879 where with that value there is a relationship between the independent variable and the dependent variable is 87.9%. This means that internal audit, supervision and control have a strong relationship to the prevention of cash fraud at the Meuraxa Health Center, Banda Aceh City. Meanwhile the coefficient of determination (R2) obtained with a value of 0.772 means that 77.2% changes in the dependent variable (cash fraud prevention) can be explained by changes in internal audit, supervision and control factors. While the rest of 11.3% is explained by other factors outside the variables of this study